Principles of corporate finance - Brealey, Richard A.; Myers, Stewart C. (New York : McGraw-Hill, 1996)
This book is about: Value; Risk; Practical problems in capital budgeting; Financing decisions and market efficiency; Dividend policy and capital structure; Options; Debt financing; Financial planning; Short-Term financial decisions; ...
Keywords: Finance; Corporations; Corporations -- Finance